Predictors of Employee Performance at Electronic Manufacturing Company: Job Satisfaction as Mediation - Ahmad Azmy; Hitler Sigalingging (Bina Nusantara University, 2025)
Performance results can ensure a long-term business sustainability. Performance can be achieved with key factors in the scope of leadership, culture, and motivation. The research analyzed the effects of work motivation, transformational leadership, and organizational culture on employee performance, mediated by job satisfaction. The research focused on examining both direct and indirect implications within the model. The research was conducted in automotive manufacturing companies. The sampling technique employed purposive sampling, targeting employees with at least one year of tenure and those directly involved in business processes. Data collection was carried out using a questionnaire distributed via Google Forms, with a total of 177 respondents. Then, Structural Equation Modeling - Partial Least Squares (SEM-PLS) was used for hypothesis testing within the research model. The findings reveal that work motivation and organizational culture significantly affect job satisfaction, whereas transformational leadership does not. Job satisfaction positively influences employee performance. Then, work motivation and organizational culture indirectly impact employee performance through job satisfaction. However, transformational leadership does not have an indirect effect on employee performance through job satisfaction. The formation of job satisfaction can act as a generator for achieving high-quality performance. The implementation of transformational leadership should be evaluated against leadership styles that meet organizational needs. Motivation and culture should be considered key factors in enhancing employee performance.